Deinococcus radiodurans UWO298 Dependence on Background Radiation for Optimal Growth - Castillo, Hugo; Li, Xiaoping; Smith, Geoffrey B. (Frontiers in Genetics, 2021)
Ionizing radiation is a major environmental variable for cells on Earth, and so organisms have adapted to either prevent or to repair damages caused by it, primarily from the appearance and accumulation of reactive oxygen species (ROS). In this study, we measured the differential gene expression in background ionizing radiation-deprived Deinococcus radiodurans cultures by growing the cells at the Low Background Radiation Experiment (LBRE) laboratory, reducing the dose rate from 72.1 to 0.9 nGy h-1 from control to treatment, respectively. This reduction in IR dose rate delayed the entry into exponential phase of the IR-shielded cultures, resulting in a lower biomass accumulation for the duration of the experiment. The RNASeq-based transcriptome analysis showed the differential expression of 0.2 and 2.7 % of the D. radiodurans genome after 24 and 34 h of growth in liquid culture, respectively. Gene expression regulation after 34 h was characterized by the downregulation of genes involved in folding newly synthesized and denatured/misfolded proteins, in the assimilation of nitrogen for aminoacids synthesis and in the control of copper transport and homeostasis to prevent oxidative stress. We also observed the upregulation of genes coding for proteins with transport and cell wall assembly roles. These results show that D. radiodurans is sensitive to the absence of background levels of ionizing radiation and suggest that its transcriptional response is insufficient to maintain optimal growth.